Bibliometric Analysis of Studies on Refugee/Immigrant/Asylum Seeker Students - Mehmet Emin Usta; Ümit Doğan (Sakarya University Journal of Education)
The aim of the study was to examine the studies published on the concept of refugee/immigrant/refugee student in terms of their bibliometric characteristics. The research was carried out in the descriptive survey model. In the study, the bibliometric method was used to examine the publication outputs and the basic structure of the field. As a result of the data from the Web of Science (WoS) database on refugee/immigrant/refugee student, 497 studies were analyzed. Within the scope of the research, descriptive statistics for the descriptive structure of the refugee/immigrant/refugee student concept, analyzes showing the distribution of publications by country, descriptive statistics of influential authors, articles and journals, co-author analyzes to reveal the social structure of the literature on the concept of refugee/immigrant/refugee student. In order to reveal the conceptual structure, trend topic analyzes, strategic diagram and word cloud analyzes were used. As a result of the research, while not much research was done between 1980 and 2008, it was determined that there was a rapid increase in the number of studies as of 2009. As a result of the research, it was concluded that the United States of America is the country that publishes the most on refugee/immigrant/asylum-seeking students. It has been concluded that the research conducted by Refugee/immigrant/asylum-seeking students in schools has the most references.